1990
DOI: 10.1080/10473289.1990.10466789
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Explanation of the Lognormality of Pollutant Concentrations

Abstract: Investigators in different environmental fields have reported that the concentrations of various measured substances have frequency distributions that are lognormal, or nearly so. That is, when the logarithms of the observed concentrations are plotted as a frequency distribution, the resulting distribution is approximately normal, or Gaussian, over much of the observed range. Examples include radionuclides in soil, pollutants in ambient air, indoor air quality, trace metals in streams, metals in biological tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
171
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(197 citation statements)
references
References 5 publications
19
171
0
3
Order By: Relevance
“…Besides the 10th, 50th, and 90th percentiles, the 95th percentile was also specified to reflect the asymmetry of the distribution and to focus on persons with high exposure. Since statistical tests revealed that the data are log -normally distributed, which is in agreement with a general result concerning the distribution of environmental concentrations (Ott, 1990 ), the GM rather than the arithmetic mean was preferred to characterise the mean location of the data. Moreover, a 95% confidence interval for the GM (CI -GM ) was added to assess the estimation error of GM.…”
Section: Methodssupporting
confidence: 64%
“…Besides the 10th, 50th, and 90th percentiles, the 95th percentile was also specified to reflect the asymmetry of the distribution and to focus on persons with high exposure. Since statistical tests revealed that the data are log -normally distributed, which is in agreement with a general result concerning the distribution of environmental concentrations (Ott, 1990 ), the GM rather than the arithmetic mean was preferred to characterise the mean location of the data. Moreover, a 95% confidence interval for the GM (CI -GM ) was added to assess the estimation error of GM.…”
Section: Methodssupporting
confidence: 64%
“…An additional reason for using this convention was to estimate doses and lung burdens for NSWs in the same manner as those estimated for SWs in previous publications. Because chemical concentrations in studies of this nature tend to be lognormally distributed (Ott, 1990 ) , the Kolmogorov ±Smirnov goodness-of -fit test (Lilliefors option) was applied to determine whether the concentration data from NSWs followed the lognormal distribution. In the earlier work on cells 1 and 3, UVPM was shown to be lognormally distributed, and nicotine was lognormal in cell 3 but not in cell 1 ( LaKind et al, 1999c ) .…”
Section: Methodsmentioning
confidence: 99%
“…We will assume that the CRs are log-normally distributed. This assumption is based on arguments of the log normality of concentrations of elements in the environment (Ott 1990(Ott , 1995, empirical observations of element concentrations in the environment that are used for calculation of CR values (Nordén et al, 2010) and the fact that the quotient of two log normal random variables is log normally distributed.…”
Section: Estimation Of Distribution Parameters Using Bayesian Inferencementioning
confidence: 99%
“…The underlying data for species with N>2 was assessed to be approximately log normally distributed by visual inspection of quantile-quantile plots. Based on these observations and also the theoretical consideration such as those addressed by Ott (1990Ott ( , 1995) the log normal assumption was also used for the two species with N=2. All statistical analyses for this example have been conducted using the BABAR software package which can be downloaded at no charge from the website: http://facilia.se/projects/babar.asp.…”
Section: Illustrative Examplesmentioning
confidence: 99%